The conflict of the working relationship in the knowledge economy: an identity perspective - Rojas Rojas, William; Stombol, Laurent (Cuadernos de Administración, 2009)
This article aims at showing the permanence ofconflictual labour relations between leaders andsubordinates within the most advanced firms ofthe developped economies. The conflictual character of labour relations is described from anidentity perspective founded on thepsychoanalytic concept of inhumanity. Theinhumanity is defined as the dimension of thehuman condition that drives individuals to affirmtheir identities by partially denying the humanconditions of the other individuals in labourrelations. The authors are willing to show themanagerial illusion that command to put in placeprogrammes aiming at preventing conflicts inlabour relations. For the authors, suchprogrammes will not eliminate an inhumanityengraved in the formal structures as well as in thecultural, symbolic and imaginary system oforganisations. The permanence of inhumanity inlabour relations reflects the existence of powerfull psychological and cultural barriers to fullyrecognising the human condition inorganisations. The impossibility to expressalterity of one’s identity in the organisational fieldsurely conducts to move the aggressive drivetowards forms of violence that are no longersymbolic but concrete. Against violence,management has no grip and no tools. As showsthe history of humanity, only civilisation andculture can lead to better recognition andrecognise oneself in alterity.